ChemInform Abstract: Synthesis of Homoallylic Amines and Acylhydrazides by Tin Powder‐Promoted Multicomponent One‐Pot Allylation Reactions. Issue 42 (September 2016) - Ma, Junyan; Huang, Danfeng; Wang, Ke‐Hu; Xu, Yanli; Chong, Siying; Su, Yingpeng; Fu, Ying; Hu, Yulai
Abstract: N‐Acylhydrazines are found to be more reactive than amines.They can not only react with aldehydes but also with ketones to give corresponding N‐homoallylic hydrides.